X-5 3/4 = -12 1/6

X-5 3/4 = -12 1/6

  • Х-5 3/4 = -12 1/6
    х = 5 3 / 4-12 1/6
    х = 5 18 / 24-12 4/24
    х = -6 10/24
    х = -6 5/12

    х-6 2/3 = -13 5/6
    х = 6 4 / 6-13 5/6
    х = -7 1/6

  • 1) х -5 (3/4) = - 12 (1/6)
    Х = - 12 (1/6) + 5 (3/4)
    Х = -11 (14/12) + 5 (9/12)
    Х = - 6 (5/12)
    Відповідь - 6 (5/12)
    2) х - 6 (2/3) = -13 (5/6)
    Х = - 13 (5/6) + 6 (4/6)
    Х = - 7 (1/6)

Добавить комментарий

Ваш e-mail не будет опубликован. Обязательные поля помечены *

6 + 3 =